Quantifying the cooling effect of rain events on outdoor thermal comfort in the southern coastal stations of the Caspian Sea. (October 2020) - Roshan, Gholamreza; Moghbel, Masoumeh
Abstract: Pleasant outdoor thermal conditions depend on a wide range of climatic elements. The impact of rainfall events, as important climatic elements, on providing thermal comfort, has been less explored in the available literature. The work presented herein investigates the impact of Rainy Days as well as a Day Prior to (Dprior ) and a Day Post rain (Dpost ) events on thermal conditions in the southern coastal region of the Caspian Sea. In this study, rainfall events during 1961–2017 observational period were categorized based on their intensity. Then, human thermal comfort during non-rainy (sunny) and rainy days was estimated and compared by using the radiation-driven Physiological Equivalent Temperature (PET) index, Universal Thermal Climate Index (UTCI) and Perceived Temperature (PT) index. Furthermore, difference between the average of thermal conditions in rainy days compared to a day prior and a day post rain events was calculated separately for comfort, cold and heat stress thresholds of each bioclimatic index. Finally, the correlation between the average of indices for rainy days and the frequency of rainfall events of each specific year was computed. Results suggested that overall average of studied indices for all rainy days is lower than the average for days prior and post the rain events. PET index has shown to be most impacted and reduced as a result of rain events and therefore more indicative of a cool ing effect. The observed difference in total average of PET in rainy days compared to non-rainy days were 8.30 °C, 5.86 °C and 8.85 °C for Babolsar, Rahst and Gorgan stations, respectively. Generally, the cooling effect of rain events on the temperature for a day prior rain events is higher than a day post rainfall. Finally, the trend analysis on rainy days in the studied period revealed that the average of bioclimatic indices in western stations (Babolsar and Rasht) are increasing whereas a decreasing trend was observed for Gorgan as more of an eastern station. Highlights: Rain events can influence the public health in outdoor spaces of coastal regions. Rainfall on its own is an atmospheric phenomenon that alters the thermal condition of our environment. Cooling effect of rain events can affect thermal comfort, heat and cold stress conditions. Biochemical conditions change during, before and after rain events.